Artificial floating islands as a tool for the water quality improvement of fishponds - Osti,João Alexandre Saviolo (2021)
Abstract In this study, the ecotechnology artificial floating islands (AFIs), colonized by Eichhornia crassipes, have been tested as a tool for water quality improvement of fishponds. The experiment was carried out in semi-intensive production during the grow-out period of Nile tilapia, comprising one production cycle. It was completely randomized with two treatments (with and without AFIs) and three replications. Temperature, dissolved oxygen, conductivity, pH, turbidity, total dissolved solids (TDS), transparency (Secchi) and concentrations of chlorophyll a (CL a), total nitrogen (TN), total ammonia nitrogen (TAN), total phosphorus (TP) and orthophosphate (PO4 3--P) were analyzed fortnightly in the fishponds. Two groups ordered based on environmental characteristics were formed by applying the Principal Component Analysis (70.68% of explicability). The fishponds with AFIs were assigned to higher values of Secchi and lower values of pH, turbidity, TDS and concentrations of nutrients. On the other hand, the fishponds without AFIs were assigned to the highest values of these variables, except for Secchi. In 30 days, the AFIs showed the lowest concentrations of TP and PO4 3--P, and for CL a, TN and TAN, the differences were recorded after 90 days. The use of AFIs has demonstrated potential to conserve water quality in fishponds, notably for biologically assimilable elements (PO4 3--P and TAN) and for those directly related to eutrophication (P and N). Artificial floating islands should be encouraged for small and medium-sized farmers as tool to improve water quality in fishponds. However, new AFIs coverage rates must be evaluated, as well as the control of hydraulic retention rates.